2018
DOI: 10.1021/acs.analchem.8b01351
|View full text |Cite
|
Sign up to set email alerts
|

Fused Silica Microcapillaries Used for a Simple Miniaturization of the Electrified Liquid–Liquid Interface

Abstract: Short pieces of fused silica capillary tubing were used to support an electrified liquid–liquid interface. A methyl deactivated silica capillary having a diameter of 25 μm was filled with 1,2-dichloroethane solution and served as the organic part of the liquid–liquid interface. A nondeactivated fused silica capillary having a diameter of 5, 10, or 25 μm was filled with an aqueous HCl solution and served as the aqueous part of the electrochemical cell. For the latter, silanization of the capillary interior with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…Analysis of obtained data confirms that these electrodes have near-unity relative area of the electrochemically active surface and show almost no kinetic hindrance to the interfacial charge transfer. Electrochemical cells derived from the presented design are currently being applied to investigate electrochemical properties of biologically active compounds at polarized liquid-liquid interfaces [34 , 73 , 74] . In response to current healthcare crisis due to Covid 19, microchannels based on architectures developed in this work are being integrated within lab-on-a-chip microfluidic devices dedicated to the analysis of human viruses [75 , 76] .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of obtained data confirms that these electrodes have near-unity relative area of the electrochemically active surface and show almost no kinetic hindrance to the interfacial charge transfer. Electrochemical cells derived from the presented design are currently being applied to investigate electrochemical properties of biologically active compounds at polarized liquid-liquid interfaces [34 , 73 , 74] . In response to current healthcare crisis due to Covid 19, microchannels based on architectures developed in this work are being integrated within lab-on-a-chip microfluidic devices dedicated to the analysis of human viruses [75 , 76] .…”
Section: Resultsmentioning
confidence: 99%
“…Both reference Ag|AgCl electrodes were connected to aqueous phases (w) and (w′) via the Luggin capillary with the tip filled with the aqueous agar gel containing 100 mM LiCl. The supported IL membrane was prepared by impregnating a polyvinyliden fluoride microporous filter (type GVHP 1300, pore size of 0.22 μm, thickness of ≈112 μm, Millipore, USA) with TDMATFPB [16] . The membrane disk (∅ 0.9 cm) was cut off from the impregnated filter and mounted in a home‐made four‐electrode cell [22] .…”
Section: Methodsmentioning
confidence: 99%
“…The supported IL membrane was prepared by impregnating a polyvinyliden fluoride microporous filter (type GVHP 1300, pore size of 0.22 μm, thickness of � 112 μm, Millipore, USA) with TDMATFPB. [16] The membrane disk (∅ 0.9 cm) was cut off from the impregnated filter and mounted in a home-made fourelectrode cell. [22] The membrane area exposed to the aqueous electrolyte solution was 0.070 cm 2 .…”
Section: Voltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only a few analytical methods have been developed for the quantitative determination of Clo, mainly using chromatographic techniques, such as reversed phase high-performance liquid chromatography with UV detection (RPÀ HPLCÀ UV) [2], high-performance liquid chromatography with UV detection (HPLCÀ UV) [1], ultra-high-performance liquid chromatography with tandem mass spectrometry (UHPLCÀ MS/ MS) [3], gas chromatography-negative-ion chemical-ionization mass spectrometry (GCÀ NICIÀ MS) [4], liquid chromatography with matrix solid phase dispersion (MSPDÀ LC) [5], and liquid chromatography with reversed phase solid phase extraction (RPÀ SPEÀ LC) [6] in the following samples: beef [1], milk [1,3,5,6], egg [3], honey [3], muscle [3], cattle kidney [4], and commercial formulation [2]. However, electrochemical techniques can be successfully applied as a reliable tool in the quantitative analysis of pesticides [7][8][9], antibiotics [7,[10][11][12], drugs [13][14][15], and other substances requiring constant controlling [15][16][17][18][19]. To our knowledge, no previous electrochemical study of Clo have been reported in the literature so far.…”
Section: Introductionmentioning
confidence: 99%